Bush’s Bible as a Liberal Bible: (Strange Though that Might Seem) - Sherwood, Yvonne (Postscripts: The Journal of Sacred Texts, Cultural Histories, and Contemporary Contexts, 2007)
This essay introduces the four articles collected in this issue of Postscripts as a forum on the theme, “Bush’s Bible.” It also argues that Bush’s Bible can be explained as an example of the “Liberal Bible,” a Bible invented in early modernity, though often misunderstood as expressing the Christian Bible’s original, true nature. The recent history of the Liberal Bible needs to be told and analysed in order to understand the fudged religious–secular compromises of modernity. The very vagueness of Bush’s Bible as a loose repository of principles is a symptom of the paradoxical place of the Bible in modern democratic-(Christian) states.